Cardiovascular risk and the COVID-19 pandemic: a population-based and case‒control studies - Małgorzata Chlabicz; Jacek Jamiołkowski; Marlena Dubatówka; Sebastian Sołomacha; Magdalena Chlabicz; Natalia Zieleniewska; Paweł Sowa; Anna Szpakowicz; Anna M. Moniuszko-Malinowska; Robert Flisiak; Marcin Moniuszko; Karol A. Kamiński (BMC, 2024)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic is associated with increases in morbidity and mortality worldwide. The mechanisms of how SARS-CoV-2 may cause cardiovascular (CV) complications are under investigation. The aim of the study was to assess the impact of the COVID-19 pandemic on CV risk. Methods These are single-centre Bialystok PLUS (Poland) population-based and case‒control studies. The survey was conducted between 2018 and 2022 on a sample of residents (n = 1507) of a large city in central Europe and patients 6-9 months post-COVID-19 infection (n = 126). The Systematic Coronary Risk Estimation 2 (SCORE2), the Systematic Coronary Risk Estimation 2-Older Persons (SCORE2-OP), the Cardiovascular Disease Framingham Heart Study and the LIFEtime-perspective model for individualizing CardioVascular Disease prevention strategies in apparently healthy people (LIFE-CVD) were used. Subsequently, the study populations were divided into CV risk classes according to the 2021 ESC Guidelines on cardiovascular disease prevention in clinical practice. Results The study population consisted of 4 groups: a general population examined before (I, n = 691) and during the COVID-19 pandemic (II, n = 816); a group of 126 patients post-COVID-19 infection (III); and a control group matched subjects chosen from the pre-COVID-19 pandemic (IV). Group II was characterized by lower blood pressure, low-density lipoprotein cholesterol (LDL-c) and high-density lipoprotein cholesterol (HDL-c) values than group I. Group III differed from the control group in terms of lower LDL-c level. There was no effect on CV risk in the general population, but in the population post-COVID-19 infection, CV risk was lower using FS-lipids, FS-BMI and LIFE-CVD 10-year risk scores compared to the prepandemic population. In all subgroups analysed, no statistically significant difference was found in the frequency of CV risk classes. Conclusions The COVID-19 pandemic did not increase the CV risk calculated for primary prevention. Instead, it prompted people to pay attention to their health status, as evidenced by better control of some CV risk factors. As the COVID-19 pandemic has drawn people's attention to health, it is worth exploiting this opportunity to improve public health knowledge through the design of wide-ranging information campaigns.